ANALISIS PENGARUH PROFITABILITAS DAN FINANCIAL DISTRESS TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Desyana Putri; Karina Silaen (Jurnal Ilmiah Ekonomi Dan Bisnis, 2022)
The purpose of this study was to determine and analyze the effect of profitability and financial distress on the audit report lag of mining companies listed on the Indonesia Stock Exchange for the period 2014-2018. The dependent variable in this study is the audit report lag. Profitability and financial distress as independent variables. The object of this research is mining companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sampling technique used purposive sampling. The research sample consisted of 12 companies with 60 units of analysis. The data analysis method is secondary data using SPSS (Statistical Package for the Social Sciences). The results of this study indicate that profitability has a negative and significant effect on audit report lag. Financial distress has no effect on audit report lag.